Combining omental plug and patch: a simple adjunct to safer repair of Giant Prepyloric Perforation. (July 2022) - Vineet, Dwivedi; Patel, Atul; Wadiwa, Yogendra; Saxena, Arjun; Agarwal, Pawan; Sharma, Dhananjaya
Giant prepyloric perforation ( i.e size > 2 cm) is a challenging surgical problem; options include repair with an omental patch or an omental plug. Alternative methods are more complicated. However, the leak rate and mortality is unacceptably high. This prompted us to combine the omental plug and patch for an effective repair. We present a case series of five patients repaired in this fashion, all of whom had an uneventful recovery, except for one who had a superficial abdominal wound dehiscence, but there was neither post-operative leak nor mortality. The mean hospital stay was 12 days.